2013
DOI: 10.1074/jbc.m112.400408
|View full text |Cite
|
Sign up to set email alerts
|

Smad7 Protein Induces Interferon Regulatory Factor 1-dependent Transcriptional Activation of Caspase 8 to Restore Tumor Necrosis Factor-related Apoptosis-inducing Ligand (TRAIL)-mediated Apoptosis

Abstract: Background: Smad7 may have biological roles other than inhibition of TGF-␤ signaling. Results: Smad7 activates caspase 8 expression by recruiting IRF1, thereby inducing TRAIL-mediated apoptosis. Conclusion: Smad7 functions as a transcriptional coactivator of IRF1 to regulate the expression of target genes. Significance: Smad7-inducing reagents can be used as anti-cancer drugs for tumors that have defects in caspase 8 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 62 publications
(33 reference statements)
1
18
0
Order By: Relevance
“…(d) The expression of the EGFP reporter containing the 3′-UTR of IRF1 was inhibited when miR-23a was over-expressed. (e) The over-expression of IRF1 suppressed cellular proliferation and promoted apoptosis [29], [30]. (f) The expression of IRF1 was sufficient to counteract the miR-23a-mediated promotion of cellular proliferation and the repression of cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…(d) The expression of the EGFP reporter containing the 3′-UTR of IRF1 was inhibited when miR-23a was over-expressed. (e) The over-expression of IRF1 suppressed cellular proliferation and promoted apoptosis [29], [30]. (f) The expression of IRF1 was sufficient to counteract the miR-23a-mediated promotion of cellular proliferation and the repression of cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that I-SMADs may act as transcriptional co-activators that are independent of the R-SMAD signaling 41, 42 . The C-terminus of the I-SMADs has a MH2 domain that is indeed conserved among all SMAD proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Using Ucn, CRH family peptide, our recent research demonstrated that Ucn blocked normal TGFβ1‐Smad2/3 signaling through Smad7 up‐regulation, implying Ucn might inhibit Smad7 degradation to block Smad2/3 phosphorylation. It is reported that Smad7 in apoptosis‐resistant MCF‐7 cells markedly sensitized the cells to TRAIL‐induced cell death [Hong et al, ]. In other in vitro models, Smad7 are demonstrated to potentiate cell apoptosis [Lallemand et al, ; Hong et al, ; Wang et al, ].…”
Section: Discussionmentioning
confidence: 99%